Community Perception on Weather Variability in the Lake Victoria Basin, Rwanda and Uganda - Bigirimana, Celestin; Omujal, Francis; Isubikalu, Prossy; Bizuru, Elias; Obaa, Bernard; Malinga, Michael; Agea, Jacob G.; Okullo, John B. L. (International Journal of Humanities, Art and Social Studies, 2011)
The study was conducted in districts of Bugesera, Kirehe and Nyamagabe in Rwanda and Buikwe, Busia, Kamuli, Masaka and Namutumba in Uganda to explore community perceptions on weather variability. Household interviews and focus group discussions were conducted to document awareness of traditional ways of weather prediction, local indicators of weather prediction, source of knowledge, effects of weather variability as well as communities’ coping strategies. Traditionally, behavior of birds, insects, moon, clouds, and direction of wind has always been the main indicators of rainfall, drought and flood pattern prediction. The main reported sources of information were parents, elders, friends and experience. Poor crop harvest, pests and diseases, crop wilting and extinction, etc, were effects of weather variability. Coping strategies were tree conservation, irrigation, use of manure and fertilizers, use of insecticide/pesticides and anti-erosion activities, etc. Community knowledge is useful and should be integrated with other conventional methods to predict weather variability.
Keywords: Community knowledge; coping strategies; weather variability; weather prediction